2018
DOI: 10.1016/j.tcs.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Avoidability of circular formulas

Abstract: Clark has defined the notion of n-avoidance basis which contains the avoidable formulas with at most n variables that are closest to be unavoidable in some sense. The family C i of circular formulas is such that C 1 = AA, C 2 = ABA.BAB, C 3 = ABCA.BCAB.CABC and so on. For every i n, the n-avoidance basis contains C i . Clark showed that the avoidability index of every circular formula and of every formula in the 3-avoidance basis (and thus of every avoidable formula containing at most 3 variables) is at most 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…All the nice formulas considered so far in the literature are also 3-avoidable. This includes doubled patterns [12], circular formulas [9], the nice formulas in the 3-avoidance basis [9], and the minimally nice ternary formulas in Table 1 [15]. Theorem 7 ([9,15]).…”
Section: Nice Formulasmentioning
confidence: 99%
“…All the nice formulas considered so far in the literature are also 3-avoidable. This includes doubled patterns [12], circular formulas [9], the nice formulas in the 3-avoidance basis [9], and the minimally nice ternary formulas in Table 1 [15]. Theorem 7 ([9,15]).…”
Section: Nice Formulasmentioning
confidence: 99%
“…This means that no classical avoidable formula on at most three variables has avoidability index greater than 4. Recently, the exact avoidability index of every 3-minimal formula has been determined [9].…”
Section: Avoidance Basesmentioning
confidence: 99%
“…The formula xyzyx ⋅ zyxyz was proven to be 2-avoidable in [9], where it was shown that it does not occur in the image of any 5 4 + -free word over 5 letters under a particular 15uniform morphism m 15 ; see [9] for details. Unfortunately, the other members of Φ 3 that flatten to xyzyx ⋅ zyxyz all occur in the m 15 -image of some 5 4 + -free word (some prefix of the infinite 5 4 + -free word described by Moulin-Ollagnier [11], in fact).…”
Section: Minimal Formulamentioning
confidence: 99%
“…Together with the construction of a morphic binary word avoiding every conjugacy class of length at least 5 and a morphic ternary word avoiding every conjugacy class of length at least 3 [1], this settles the topic of the smallest alphabet needed to avoid every conjugacy class of length at least k.…”
Section: Introductionmentioning
confidence: 99%
“…Bell and Madill [2] obtained a pure morphic word with this property (and some additional properties) over the 12-letter alphabet. Gamard et al [1] independently obtained a morphic word over the 6-letter alphabet. They also conjectured that the alphabet size can be lowered to 5, which is best possible.…”
Section: Introductionmentioning
confidence: 99%